Plasma-beam Alignment Technique for Ferroelectric Liquid Crystals - Hegde, Gurumurthy; Yaroshchuk, Oleg; Kravchuk, Ruslan; Murauski, Anatoli; Chigrinov, V. G.; Kwok, Hoi Sing (Blackwell Publishing Ltd, 2008)
The plasma-beam alignment procedure earlier developed for the alignment of nematic liquid crystals is successfully extended to ferroelectric liquid crystals (FLC). The highly uniform alignment of the “chevron” structure (before electrical treatment of FLC cells) and “quasi bookshelf” structure (after the electrical treatment) are realized. The contrast of bistable switching larger than 350:1 is achieved. This makes the non-contact plasma-beam alignment procedure especially attractive for high-contrast bistable LCDs on an LCOS base, particularly used in PDA and e-books. Fast switching and realization of gray scale in the plasma-beam aligned FLC cellsmakes this technique also promising for full-color displays including color LCD TV.